MOLEKULARNA I BIOHEMIJSKA KARAKTERIZACIJA FAMILIJARNE HIPERHOLESTEROLEMIJE: POVEZANOST GENETSKIH VARIJANTI I LIPIDNIH PARAMETARA: GENETSKE VARIJANTE I LIPIDNI PARAMETRI U FAMILIJARNOJ HIPERHOLESTEROLEMIJI - Singh, Sandra; Gašić, Vladimir; Komazec, Jovana; Grubiša, Ivana; Popović, Ljiljana; Rasulić, Iva; Petakov, Ana; Mitrović, Marija; Mihailović, Emilija; Pavlović, Sonja; Ilić, Katarina (Journal of Medical Biochemistry, 2025)
Background: Familial hypercholesterolemia (FH) is characterised by elevated low-density lipoprotein cholesterol (LDL-C) levels and an increased risk of premature cardiovascular disease. The present study aimed to investigate the genetic background and associated biochemical profiles of patients with clinically suspected FH in Serbia. Methods: A total of 101 patients with clinically suspected FH were recruited between 2015 and 2023 from the Clinic for Endocrinology, Diabetes and Metabolic Diseases in Serbia. Clinical diagnosis was established using the Dutch Lipid Clinic Network (DLCN) criteria. Fasting serum lipids (total cholesterol [TC], LDL-C, high-density lipoprotein cholesterol [HDL-C], triglycerides [TG], apolipoprotein A-I [ApoA-I], apolipoprotein B [ApoB], and lipoprotein(a) [Lp(a)]) were measured enzymatically. Genetic testing for LDLR, APOB, PCSK9, and LDLRAP1 genes was performed using next-generation sequencing on the Illumina NextSeq 550DX platform. Variants were classified according to the American College of Medical Genetics and Genomics (ACMG) guidelines. Statistical analyses were conducted in SPSS (version 30.0).Results: Pathogenic or likely pathogenic variants were identified in 44 of 101 patients, yielding a mutation detection rate of 43.6%. Genetically confirmed FH patients exhibited significantly higher LDL-C (p